WEBINAR PENGGUNAAN DESAIN SYSTEMATIC REVIEW DALAM PELAKSANAAN PENELITIAN SELAMA PANDEMI COVID-19 DI UNIVERSITAS ESA UNGGUL - Sukarno, Anita; Azteria, Veza; Sukaesti, Diah (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Background: The Covid-19 pandemic has a negative impact on every aspect of Indonesian life. However, the learning process of academics is required to keep going. The lectures are required to conduct the three obligation of higher education, one of them is research. Webinars is delivered to present how to conduct research with a systematic review design which are seen as suitable strategies to help educators carry out the research process in the midst of the Covid-19 pandemic. Objective: to increase knowledge and skills in conducting research with a systematic review design. Method: The current virtual implementation seminar was conducted with media zoom software attended by 26 Esa Unggul University lecturers for 1 hour 30 minutes. Evaluation of participants' knowledge was carried out after a webinar consisting of 6 questions. Results: after this webinar activity, 15 of 26 participants (60%) answered all questions correctly and on average the participants answered correctly 5 of 6 evaluation questions. Conclusion: The implementation of the webinar can increase the knowledge of lectures in conducting research with a systematic review design as a suitable design alternative during the Covid-19 pandemic.Â Keywords: webinar, systematic review, research